Experimental study on the performance of Peltier TEC12706 as a cooling and heating media - Sujono Sujono; Hernawan Novianto (Jurnal Polimesin, 2024)
The application of refrigeration spans a wide range of industries, from household needs to the oil and gas sector, employing various cooling methods. One rapidly developing approach is the use of Peltier devices, particularly the TEC1 12706 model, due to its compact size and widespread availability. It is essential for students to understand the application of Peltier technology, which necessitates the creation of practical tools for both educational and research purposes. Most existing research on Peltier devices focuses on air conditioning systems with fixed loads; therefore, it is imperative to explore their cooling and heating effects in dynamic environments. To address this gap, this study investigates the performance of Peltier modules as cooling and heating systems for moving media. A prototype of a cooling and heating module (heat pump) was developed using Peltier devices, and its performance was evaluated by varying the flow rates of hot and cold water (1.62/1.02; 1.2/0.8; and 0.9/0.68 L/min) and the number of operational Peltier elements (2, 4, 6). Calculations using the relevant formulas yielded the Coefficients of Performance (COP): COPc = 0.45, COPh = 1.37, and COPtot = 1.82. The results revealed that the cooling performance coefficient is lower than both the heating and total performance coefficients. Additionally, variations in flow rates and the number of installed Peltier devices showed minimal impact on cooling and heating performance coefficients.